Zur Übersetzung juristischer Termini in deutschen und polnischen Klageanträg - Młodecki, Michał (Glottodidactica, 2001)
The present paper aimed at suggesting Polish and German equivalents of legal terms used in the petitions of suits in both languages. First the methods of translating legal terms given in the literature were presented. According to them came the catalogue of the mentioned Polish and German legal terms with the argumentation for the choice of the suggested equivalents both in Polish and German. The assumed principle was, that in the case of two different legal systems, one should, if possible, avoid translating legal terms of the source language with the parallel legal terms of the target language. The discussed legal terms and their equivalents were juxtaposed in a table as a summary.